Identification of a Functional Plasmodesmal Localization Signal in a Plant Viral Cell-To-Cell-Movement Protein - Cheng Yuan (American Society for Microbiology, 2016)
ABSTRACT Our fundamental knowledge of the protein-sorting pathways required for plant cell-to-cell trafficking and communication via the intercellular connections termed plasmodesmata has been severely limited by the paucity of plasmodesmal targeting sequences that have been identified to date. To address this limitation, we have identified the plasmodesmal localization signal (PLS) in the Tobacco mosaic virus (TMV) cell-to-cell-movement protein (MP), which has emerged as the paradigm for dissecting the molecular details of cell-to-cell transport through plasmodesmata. We report here the identification of a bona fide functional TMV MP PLS, which encompasses amino acid residues between positions 1 and 50, with residues Val-4 and Phe-14 potentially representing critical sites for PLS function that most likely affect protein conformation or protein interactions. We then demonstrated that this PLS is both necessary and sufficient for protein targeting to plasmodesmata. Importantly, as TMV MP traffics to plasmodesmata by a mechanism that is distinct from those of the three plant cell proteins in which PLSs have been reported, our findings provide important new insights to expand our understanding of protein-sorting pathways to plasmodesmata. IMPORTANCE The science of virology began with the discovery of Tobacco mosaic virus (TMV). Since then, TMV has served as an experimental and conceptual model for studies of viruses and dissection of virus-host interactions. Indeed, the TMV cell-to-cell-movement protein (MP) has emerged as the paradigm for dissecting the molecular details of cell-to-cell transport through the plant intercellular connections termed plasmodesmata. However, one of the most fundamental and key functional features of TMV MP, its putative plasmodesmal localization signal (PLS), has not been identified. Here, we fill this gap in our knowledge and identify the TMV MP PLS.